PERENCANAAN KARAKTERISTIK RUANG PARKIR KENDARAAN PADA SMA (SLUA) SARASWATI 1 DENPASAR - I Gusti Agung Gde Suryadarmawan; Ni Ketut Sri Astati Sukawati; I Ketut Sudipta Giri; I Ketut Olgi Aditya Surya (Program Studi Teknik Sipil Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
The problem of parking is very important to be studied more deeply, because almost all activities in open spaces require parking facilities. The required parking space must be provided adequately. On street parking is parking that takes place along the body of the road. This has a negative impact on the smooth flow of traffic, because it causes a reduction in the width of the road that is traversed. The aim of this research is to determine the characteristics of motorized vehicle parking and the shape of the parking angle pattern by considering the incidence of side friction factors. The vehicle parking area at Saraswati 1 Denpasar Senior High School has not received a touch of planning and arrangement, so this condition causes vehicle chaos and difficulty parking for users to get out and enter the parking location. By making a parking arrangement plan at the school, it is hoped that it will be able to accommodate the number of parked vehicles and facilitate access in and out of the vehicles themselves.